The determinants of non-tariff barriers: the role of WTO membership - Lee, Chin; Che Rusli, Ahmad Khusyairi (Faculty of Economics and Management, Universiti Putra Malaysia, 2015)
With the formation of the WTO/GaTT, a substantial reduction of tariff barriers (TBs) was achieved, but many countries then tried to use more non-tariff barriers (nTBs) to achieve new trade protection. To date, about two-thirds of the countries in the world are members of WTO. This study aims to find the determinants of NTBs and ascertain whether the accession as a member of WTO can actually reduce the use of nTBs. The results indicate that WTO membership, tariff and unemployment exert a strong influence on the incidence of NTBs, while the exchange rate, political institution and economic size are not significant factors. In addition, tariffs and NTBs are complementary. The finding also reveals that WTO member use NTBs to a lesser degree than do non-members of the WTO. hence, we can conclude that accession to membership in the WTO reduces the use of nTBs.